MAKNA SIMBOLIK KETAWANG UNDUR-UNDUR KAJONGAN DALAM UPACARA TINGALAN JUMENENGAN DALEM DI KARATON SURAKARTA - Rival Sandhika Hermawan; Nil Ikhwan (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2024)
Ketawang Undur-Undur Kajongan is a gending pakurmatan relic of Sultan Agung during the Islamic Mataram kingdom for the purpose of the tingalan jumenengan ceremony, and presented at the jengkar dalem procession. The use of Ketawang Undur-Undur Kajongan for the tingalan jumenengan ceremonies was continued by the Surakarta Kasunanan Palace for the jengkar dalem of Susuhunan Pakubuwana. Ketawang Undur-Undur Kajongan specifically to honor the king and only with the king's permission Ketawang Undur-Undur Kajongan can be performed. The use of gambang gangsa instruments in the gamelan ageng instrument makes Ketawang UndurUndur Kajongan has an own unique and also becomes one of the categories of gending pamijen. Ketawang UndurUndur Kajongan has two functions as a symbolic representation of the king's greatness, as well as a marker in the tingalan jumenengan ceremony. To dissect the problems in the material object, researcher uses a qualitative method with observation, interview and data analysis. Using the theory of music function by Alan P. Merriam with using two elements of function, namely the function of music as communication and the function of music as a symbol representation, as well as the semiotic theory of Marcel Danesi to sharpen the argument about symbolism. Chapter two discusses an overview of Surakarta Palace and an overview of the tingalan jumen ceremony. Overview of the tingalan jumenengandalem ceremony, chapter three discusses the the structure of Ketawang Undur-Undur Kajongan from the point of view of musical communication in the ceremony, and chapter three. Musical communication in the ceremony, and chapter four discusses the symbolic meaning of Ketawang Undur-Undur Kajongan.